2014
DOI: 10.1371/journal.pone.0090131
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Lozenge for Oral Transmucosal Delivery of Trans-Resveratrol in Humans: Proof of Concept

Abstract: Resveratrol provides multiple physiologic benefits which promote healthspan in various model species and clinical trials support continued exploration of resveratrol treatment in humans. However, there remains concern regarding low bioavailability and wide inter-individual differences in absorption and metabolism in humans, which suggests a great need to develop novel methods for resveratrol delivery. We hypothesized that oral transmucosal delivery, using a lozenge composed of a resveratrol-excipient matrix, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…45,46 Furthermore, different administration route was also studied, such as intravenous administration and oral transmucosal delivery. 47,48 Another method was inhibition of metabolism. As reported by Johnson and his colleagues, 49 combination of resveratrol with UGT inhibitor piperine gave 1000% increase of peak plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Furthermore, different administration route was also studied, such as intravenous administration and oral transmucosal delivery. 47,48 Another method was inhibition of metabolism. As reported by Johnson and his colleagues, 49 combination of resveratrol with UGT inhibitor piperine gave 1000% increase of peak plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, only a small fraction of orally administered resveratrol escapes biotransformation in vivo, even under high‐dose supplementation, which has been proposed as a major hurdle for reaching effective systemic concentrations . Of note, in a proof‐of‐concept study with two healthy men, relatively high plasma concentrations of free resveratrol (1.4 μmol L −1 ) were achieved by delivering trans ‐resveratrol (140 mg) in lozenges through absorption via the oral mucosa, which circumvents first‐pass metabolism in the intestine and liver …”
Section: Discussionmentioning
confidence: 99%
“…[11] Of note, in a proof-of-concept study with two healthy men, relatively high plasma concentrations of free resveratrol (1.4 μmol L −1 ) were achieved by delivering trans-resveratrol (140 mg) in lozenges through absorption via the oral mucosa, which circumvents first-pass metabolism in the intestine and liver. [23] Several novel formulations have attempted to enhance the bioavailability of resveratrol, mostly by means of increasing its hydrophilicity, stability, and bioaccesibility, including: micronization, microencapsulation with polymeric nanoparticles and solid lipid nanoparticles, encapsulation into colloidal lipidand/or biopolymer-based delivery systems (liposomes, micelles, nanoemulsions and microemulsions), complexation with cyclodextrins, and encapsulation into pectinate beads, to name a few. [8,[11][12][13][14]24] Food-grade surfactant-based micelles may constitute a relatively easy and cost-effective way for the solubilization of hydrophobic molecules due to their spontaneous self-assembly intro structures with a hydrophobic core and a hydrophilic outer shell.…”
Section: Discussionmentioning
confidence: 99%
“…Oral transmucosal administration is another route being investigated (Ansari et al, 2011;Blanchard et al, 2014). A proof of concept study on the formulation of resveratrol-excipient lozenges investigated the solubility of the resveratrol-excipient matrices in water; and a bioavailability experiment with two healthy male participants was performed (Blanchard et al, 2014). The study demonstrated that the resveratrol-ribose lozenges had superior solubility compared to other resveratrol-excipient lozenges tested (Blanchard et al, 2014).…”
Section: Alternative Routes Of Administrationmentioning
confidence: 99%